2017
DOI: 10.3390/molecules22111977
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Potential of 1-Nitro-2-Phenylethylene

Abstract: Inflammation is a reaction of the host to infectious or sterile stimuli and has the physiological purpose of restoring tissue homeostasis. However, uncontrolled or unresolved inflammation can lead to tissue damage, giving rise to a plethora of chronic inflammatory diseases, including metabolic syndrome and autoimmunity pathologies with eventual loss of organ function. Beta-nitrostyrene and its derivatives are known to have several biological activities, including anti-edema, vasorelaxant, antiplatelet, anti-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Controlling neutrophil numbers via apoptosis can alleviate tissue injury. 35 Neutrophils secrete MPO to delay their own apoptosis and promote their accumulation through the ERK and Akt pathways. 36 , 37 We showed that MPO expression is upregulated in lung tissue after CS exposure and that this CS-induced upregulation is reversed by AMD3100 treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Controlling neutrophil numbers via apoptosis can alleviate tissue injury. 35 Neutrophils secrete MPO to delay their own apoptosis and promote their accumulation through the ERK and Akt pathways. 36 , 37 We showed that MPO expression is upregulated in lung tissue after CS exposure and that this CS-induced upregulation is reversed by AMD3100 treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Various nitro(NO 2 )‐based analogues are privileged moieties. These analogues have a wide range of biological activities, including anti‐kinetoplastid (Rodriguez Arce et al, 2017; Brancaglion et al, 2018; Papadopoulou et al, 2012; Elias et al, 2016; Papadopoulou, Bloomer, Rosenzweig, Arena, et al, 2014, Papadopoulou et al, 2015, Papadopoulou et al, 2016; Patterson & Wyllie, 2014; Scarim & Chin, 2019; Silva et al, 2016), anthelmintic (Balaji et al, 2014; Dutta, 2014; Fonseca‐Berzal et al, 2016; Moreno & Docampo, 1985; Satyendra et al, 2015), anti‐malarial (Bekhit et al, 2012; Dohutia et al, 2017; Labaied et al, 2004; Malebo et al, 2020; Maroziene et al, 2019; Roberts et al, 2017), antifungal (Kang et al, 2019; Sadeghpour et al, 2017; Zhu et al, 2017), anti‐proliferative (Ahmad et al, 2007; Chinnapaka et al, 2019; Cho et al, 2020; Cuartas et al, 2019; Dunlap et al, 2008; Sakanyan et al, 2014; Shimamura et al, 2003), antimicrobial (Abd El‐Salam et al, 2015; Alasmary et al, 2015; El Azab & Elkanzi, 2020; El‐Hossary et al, 2018; Kozłowska et al, 2019; Kucerova‐Chlupacova et al, 2016; Mladenović et al, 2010; Serban et al, 2018; Sivasankerreddy et al, 2018; Teran et al, 2019), anti‐Alzheimer (Semenov et al, 2020), anti‐inflammatory (El‐Haggar & Al‐Wabli, 2015; Januario et al, 2018; Liu et al, 2019; Rubbo, 2013; Sugimoto et al, 2017; Theodosis‐Nobelos et al, 2020; Tratrat et al, 2021; Tseng et al, 2018), antioxidant (Alshibl et al, 2020; Gallardo et al, 2016…”
Section: Nitro‐based Compounds In Medicinal Chemistrymentioning
confidence: 99%
“…The assays were performed according to Sugimoto et al [44] using human monocyte-like cell line THP-1 obtained from ATCC. THP-1 cells were cultured in RPMI 1640 medium supplemented with 10 % v/v heat-inactivated FBS and antibiotics (100 µg/mL streptomycin and 100 U/mL penicillin).…”
Section: Cell Culture and In Vitro Assaymentioning
confidence: 99%
“…Western blot analyses THP-1 cells were washed with PBS and the whole-cell extracts were prepared as previously described [44,45]. Protein concentrations were quantified with Bradford reagent.…”
Section: Cell Culture and In Vitro Assaymentioning
confidence: 99%